Revisiting effects of teacher characteristics on physiological and psychological stress: a virtual reality study - Bardach, L; Huang, Y; Richter, E; Klassen, RM; Richter, D (Springer Nature, 2023)
Identifying personal characteristics associated with teachers’ stress is a longstanding research goal with important implications for practice. The present work revisits the effects of individual characteristics in terms of neuroticism, classroom management self-efficacy, and cognitive (reasoning) abilities on stress using virtual reality (VR). Relying on a sample of 56 German pre-service teachers (Mage = 22.73, SDage = 4.93; 50.9% females), we capitalized on a VR classroom environment that allowed the integration of experimental control and authentic teaching situations, where pre-service teachers responded to the disruptive behaviors of the student avatars. We focused on stress responses in terms of psychological stress (self-reported stress) assessed after the VR session, and physiological stress (heart rate) assessed during the VR session. A total of 30 (26) participants was assigned to a condition with higher (lower) levels of disruptive student behavior, referred to as higher and lower complexity condition, respectively. Results from linear mixed-effects models revealed that neuroticism positively predicted psychological and physiological stress responses in pre-service teachers, whereas classroom management self-efficacy and cognitive (reasoning) abilities were not significantly related to stress responses. Level of complexity and the interaction between complexity and individual characteristics did not have an effect. This study underlines the value of VR as a tool for psychological research and contributes to existing knowledge on teacher characteristics and stress.